2016
DOI: 10.1016/j.diagmicrobio.2016.07.023
|View full text |Cite
|
Sign up to set email alerts
|

A molecular epidemiological study of human parainfluenza virus type 3 at a tertiary university hospital during 2013–2015 in Catalonia, Spain

Abstract: Human parainfluenza virus type 3 (HPIV-3) is one of the most common respiratory viruses particularly among young children and immunocompromised patients. The seasonality, prevalence and genetic diversity of HPIV-3 at a Spanish tertiary-hospital from 2013 to 2015 are reported. HPIV-3 infection was laboratory-confirmed in 102 patients (76%, under 5 years of age). Among <5 years-old patients, 9 (11.5%) were under any degree of immunosuppression, whereas this percentage was significantly higher (19; 79.2%) among p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 31 publications
3
9
0
Order By: Relevance
“…However, distribution of the distances in our study was similar to those in previous reports of the HRV3 F gene (Tsutsui et al, 2017), and also the HRV3 HN gene (Mao et al, 2012). This implied that the F and HN genes may be categorized into the same cluster and subcluster (Godoy et al, 2016;Košutić-Gulija et al, 2017). In addition, the genetic distances of the HRSV-A and HRSV-B F gene based on globally collected strains were also smaller than the present study, reported as 0.025 and 0.017, respectively (Kimura et al, 2016(Kimura et al, , 2017.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…However, distribution of the distances in our study was similar to those in previous reports of the HRV3 F gene (Tsutsui et al, 2017), and also the HRV3 HN gene (Mao et al, 2012). This implied that the F and HN genes may be categorized into the same cluster and subcluster (Godoy et al, 2016;Košutić-Gulija et al, 2017). In addition, the genetic distances of the HRSV-A and HRSV-B F gene based on globally collected strains were also smaller than the present study, reported as 0.025 and 0.017, respectively (Kimura et al, 2016(Kimura et al, , 2017.…”
Section: Discussionsupporting
confidence: 90%
“…These findings may contribute to a better understanding of HRV3 infection in humans. Some molecular epidemiological studies of the HRV3 F gene have been reported (Godoy et al, 2016;Košutić-Gulija et al, 2017;Tsutsui et al, 2017). Godoy et al (2016) created a phylogenetic tree based on the partial sequence of the F gene (390 nt) by the neighbor-joining method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several antigenic epitopes of the HN glycoprotein have been previously characterized. 12,13 Three amino acid substitutions in antigenic epitopes were found in this study, including K168R (16.67%), H295Y (100%), and I391V (100%). In particular, the K168R mutation locates very close to amino acids of significant importance to the integrity of distinct HN epitopes (residues 171), 14 and it has not been identified in Asia before.…”
Section: Discussionmentioning
confidence: 55%
“…2). This is especially interesting as no changes that could distinguish different phylogenetic subgroups were present when we analyzed HPIV3 F and HN proteins [40], which are more diverse, and therefore used for phylogenetic classification [41, 42]. Also, in the case of HPIV3, most of the amino acid changes in glycoproteins were restricted to cytoplasmic and transmembrane regions [40], which are regions thought to be important for interaction with the M proteins [43].…”
Section: Discussionmentioning
confidence: 99%